In Vitro Expression of the Extracellular Matrix Components Aggrecan, Collagen Types I and II by Articular Cartilage‐Derived Chondrocytes. (15th March 2016) - Schneevoigt, J.; Fabian, C.; Leovsky, C.; Seeger, J.; Bahramsoltani, M.
Summary: The extracellular matrix (ECM) of hyaline cartilage is perfectly suited to transmit articular pressure load to the subchondral bone. Pressure is transferred by a high amount of aggrecan‐based proteoglycans and collagen type II fibres in particular. After any injury, the hyaline cartilage is replaced by fibrocartilage, which is low in proteoglycans and contains collagen type I predominantly. Until now, long‐term results of therapeutic procedures including cell‐based therapies like autologous chondrocyte transplantation (ACT) lead to a replacement tissue meeting the composition of fibrocartilage. Therefore, it is of particular interest to discover how and to what extent isolation and in vitro cultivation of chondrocytes affect the cells and their expression of ECM components. Hyaline cartilage‐derived chondrocytes were cultivated in vitro and observed microscopically over a time period of 35 days. The expression of collagen type I, collagen type II and aggrecan was analysed using RT‐qPCR and Western blot at several days of cultivation. Chondrocytes presented a longitudinal shape for the entire cultivation period. While expression of collagen type I prevailed within the first days, only prolonged cultivation led to an increase in collagen type II and aggrecan expression. The results indicate that chondrocyte isolation and in vitro cultivation lead to a dedifferentiation at least to the stage of chondroprogenitor cells.